Metallapentalenofuran: Shifting Metallafuran Rings Promoted by Substituent Effects. Issue 54 (4th September 2018) - Hua, Yuhui; Lan, Qing; Fei, Jiawei; Tang, Chun; Lin, Jianfeng; Zha, Hexukun; Chen, Shiyan; Lu, Yinghua; Chen, Jiangxi; He, Xumin; Xia, Haiping
Abstract: Bulky substituents play important roles in controlling the reaction pathways or producing selected products. This work reports that the shift of metallafuran rings in a metallapentalenofuran complex can be promoted by the substituent effect via a reversible C−H bond reductive elimination and oxidative addition. The starting osmapentalyne, a so‐called 7‐carbon carbolong complex, was produced by the oxidation of a metallapentalenofuran with FeCl3 . It was then allowed to react with nucleophiles, followed by a C−H activation, to give the aforementioned metallapentalenofuran complex. This work enriches the family of carbolong complexes and reveals a new strategy to promote, but not prevent reactions by the bulky substituents. Abstract : Metallaaromatics : Treatment of metallapentalenofuran with FeCl3 in air quickly produces osmapentalyne, which can undergo a further nucleophilic reaction followed by a C−H activation to give metallapentalenofuran. The stereochemistry of its substituents dominates an interesting metallafuran ring shift under basic conditions (see scheme).